Decentralized cloud manufacturing-as-a-service (CMaaS) platform architecture with configurable digital assets. (July 2020) - Hasan, Mahmud; Starly, Binil
Graphical abstract: Highlights: Resource interaction protocol connecting clients with service providers sharing data assets. A layered middleware architecture stack through web browsers and blockchain systems. 'Smart Contracts' interaction in a cybermanufacturing information system architecture. Evaluation of Smart contracts on three Ethereum based Test Networks – Ropsten, Rinkeby and Kovan. Separation of Concerns, object oriented design and multi-signature to secure smart contracts. Abstract: Contemporary Cloud Manufacturing-as-a-Service (CMaaS) platforms now promise customers instant pricing and access to a large capacity of manufacturing nodes. However, many of the CMaaS platforms are centralized with data flowing through an intermediary agent connecting clients with service providers. This paper reports the design, implementation and validation of middleware software architectures which aim to directly connect client users with manufacturing service providers while improving transparency, data integrity, data provenance and retaining data ownership to its creators. In the first middleware, clients have the ability to directly customize and configure parts parametrically, leading to an instant generation of downstream manufacturing process plan codes. In the second middleware, clients can track the data provenance generated in a blockchain based decentralized architecture across a manufacturing system. The design of digital assets across a distributed manufacturing system infrastructure controlled by autonomous smart contracts through Ethereum based ERC-721 non-fungible tokens is proposed to enable communication and collaboration across decentralized CMaaS platform architectures. The performance of the smart contracts was evaluated on three different global Ethereum blockchain test networks with the centrality and dispersion statistics on their performance provided as a reference benchmark for future smart contract implementations.